Pendayagunaan Guru Sekolah Luar Biasa Idayu Malang dalam Deteksi Dini Gangguan Bicara dan Bahasa pada Anak - Nurdiana Nurdiana; Ni Luh Putu Herli Mastuti; Astri Proborini; Yuseva Sariati (Journal of Dedicators Community, 2021)
The increase prevalence of speech and language disorders, which greatly affects the quality of life of a child. The role of educational institutions, especially teachers, is needed in early detection of these disorders. Early detection abilities must be based on the ability to understand a child's speech and language development. Community Service Activities are carried out at the Idayu 2 Malang Special School, by providing training to teachers on speech and language development and early detection methods. The method used is the provision of material followed by an examination of the students status growth ad development. There was an increase in the teacher's ability after the activity was carried out, which was marked by an increase in the average pretest and postest results: 61.15 to 86.54. On examination of the student's growth status, the nutritional status of the majority of students was found to be good nutrition (61%), but the short stature rate was also quite large (49%). The condition of children with special needs with physical limitations greatly affects their growth and development, so that the role of the environment is needed for optimal development, including parents and educational institutions.